(untitled) (Research, Society and Development, 2021)
Objective: To analyze the perception of the nursing staff in the professional and companion/family relationship of the child hospitalized in a pediatric hospital. Methodology: We opted for a qualitative, descriptive research using the interview technique from a semi-structured script. For data analysis, the content analysis method was used. The study included 13 professionals from the nursing team, including five nurses and eight nursing technicians, from July to September 2021. Results: Two thematic nuclei were listed: barriers in the professional and companion/family relationship of the hospitalized child and strategies of strengthening for the care of hospitalized children. According to the nursing team’s narratives, the interaction, participation and emotional control of the companion are essential to subsidize care, helping the child’s recovery. The need to develop strategies to assist in the professional nursing and companion relationship was also evidenced, such as psychological support and professional qualification, as well as the effective performance of the multidisciplinary team in the care of children and their families, increasing the bond, communication and the insertion of the family member in the care process during the hospitalization period. Final Considerations: The companion is an integral part of the assistance as they are the link between the nursing team and the pediatric patient. The team must be prepared and qualified to offer humanized, empathetic and resilient assistance that significantly contributes to the child’s recovery process.